Extraction by Dry Rendering Methode and Characterization Fish Oil of Catfish Viscera Fat by Product of Smooked Fish Processing - Kamini Kamini; Pipih Suptijah; Joko Santoso; Sugeng Heri Suseno (Jurnal Pengolahan Hasil Perikanan Indonesia, 2016)
AbstractThe catfish viscera fat, is cathfish processing by-products, has potential to be used as a source of rawmaterial for production of fish oil. This study aimed to analyze the value of proximate, heavy metal contentand fatty acid profile of catfish viscera fat (Pangasius hypopthalmus) and characterized fish oil extracted bydry rendering in various temperature and time than compared it to fish oil extracted by stove heating toobtain the best treatment. Proximate, heavy metal residue, and the fatty acid profile analysis were conductedfor characterizing catfish viscera fat. Fish oil extraction was conducted by dry rendering in varioustemperatures of 50, 60, 70, 80 °C for 1, 2, and 3 hours. Fish oil quality was determined by the chemicalcharacteristics i.e. PV, FFA, anisidin and TOTOX. The results of the study showed that fat content of catfishfat viscera was 88.19 %, the heavy metals content was below SNI standart to be consumed, and fatty acidprofile composition was SFA>MUFA>PUFA. The highest fatty acid content was oleic acid. The best fish oilquality was resulted on temperature extraction of 50°C for 2 hours with yield value, PV, FFA, anisidin, andTOTOX were 45.17 %, 2.77 meq/kg, 0.83 %, 2.86 meq/kg, 8.39 meq/kg respectively. This result was notsignificantly different with fish oil extracted by the stove heating expect for yield and PV were 80.11% and6.52 meq/kg, respectively.